COMPARATIVE EFFICIENCY OF DIFFERENT FEED ADDITIVES ON THE PERFORMANCE OF QUAIL CHICKS (Biological Sciences - PJSIR, 2003)
Quail chicks, 240 days old (of mixed sex), were randomly divided into 4 groups having 3 replicates in each, and given four feeds i.e. with no additive, supplemented with zinc bacitracin only, zinc bacitracin + rumen meal and zinc bacitracin+ dried brewer’s yeast, for 42 days to determine the effect of feed additives on the growth. During experimental period, weight gain, feed efficiency and dressing percentage were recorded. Results indicated that supplementation of feed with zinc bacitracin + rumen meal and zinc bacitraicn + dried brewer’s yeast significantly improved weight gain. Feed consumption and feed efficiency ratio among various groups showed non-significant differences.